2018
DOI: 10.1097/icl.0000000000000495
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Two Orthokeratology Lens Designs and Comparison of Their Optical Effects on the Cornea

Abstract: The four- and five-curve orthokeratology lens designs generate significantly different optical modifications on the cornea. This can affect reports on orthokeratology efficacy for myopia management as well as the lens selection when used for myopia correction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…Changes in the topographic profile, including a wider, steeper midperipheral ring, and closer to the pupil center, has been hypothesized as an important factor in improving the efficacy of myopia control with OrthoK lenses [24, 27, 32]. In a study published in 2016, Kang et al suggested that inducing greater degrees of myopic defocus on the peripheral retina, more than what is habitually experienced in a typical OrthoK lens, may be required for effective myopia control [33].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the topographic profile, including a wider, steeper midperipheral ring, and closer to the pupil center, has been hypothesized as an important factor in improving the efficacy of myopia control with OrthoK lenses [24, 27, 32]. In a study published in 2016, Kang et al suggested that inducing greater degrees of myopic defocus on the peripheral retina, more than what is habitually experienced in a typical OrthoK lens, may be required for effective myopia control [33].…”
Section: Discussionmentioning
confidence: 99%
“…263 More recently, a retrospective study found that participants fit with a four-curve OK lens design demonstrated a significantly larger central distance zone of treatment compared with a five-curve lens design, but there was no difference in the power or width of the midperipheral steepened zone, and the effect on relative peripheral refraction was not measured. 264 This is an area for further research.…”
Section: Future Research Directions On Intervention and Treatment 71mentioning
confidence: 95%
“…The back optic zone diameter and reverse curve width of an ortho-k lens influence the treatment zone diameter and the surrounding annulus of mid-peripheral steepening, respectively. Manipulation of the back optic zone diameter or reverse curve width (by ≤1 mm) can produce significant variations in anterior corneal optics [79,345], with a smaller back optic zone diameter generating more relative peripheral corneal steepening and positive spherical aberration [346]. However, these lens modifications may not significantly alter peripheral refraction [74,307].…”
Section: Treatment Zone Sizementioning
confidence: 99%